Intestinal malrotation needs immediate consideration and investigation. Issue 11 (23rd November 2016) - Ezer, Semire Serin; Oguzkurt, Pelin; Temiz, Abdulkerim; Ince, Emine; Gezer, Hasan Ozkan; Demir, Senay; Hicsonmez, Akgun
Abstract: Background: The aim of this study was to evaluate clinical presentation, diagnostic studies, and volvulus rate and to describe the unusual clinical clues of intestinal malrotation. Methods: A retrospective descriptive review was carried out of all patients diagnosed with intestinal malrotation between 2002 and 2014. Patients were divided into two groups: infants (≤1 year, n = 16; group 1); and children (>1 year, n = 12; group 2). Patient demographics, clinical history, symptoms, physical examination, diagnostic work‐up, operative findings and early outcome were evaluated. Results: Bilious vomiting was the cardinal complaint in both groups. Unusual symptoms such as respiratory insufficiency, dehydration, afebrile convulsion, and lethargy were prominent symptoms in six patients in group 1, whereas history of frequent hospitalization due to recurrent abdominal pain and feeding intolerance were prominent in six patients in group 2. Midgut volvulus was identified in 15 patients, four of whom were in group 2. Standard Ladd's procedure was done in addition to correction of volvulus. Conclusion: Malrotation with or without midgut volvulus is not a rare condition and should be kept in mind for any age group. Specific signs of diagnosis are not easily identified. In the case of unusual clinical presentation, diagnosis may be delayed and can result in catastrophic consequences if intestinal perfusion occurs. Although midgut volvulus is seen most frequently in infants, risk and complication rate are high beyond 1 year of age as well, and can manifest as failure to thrive, food intolerance, and abdominal pain needing recurrent hospitalization. Diagnostic suspicion and interdisciplinary coordination are essential for timely diagnosis and surgical treatment.